Executives’ professional ties along the supply chain: The impact on partnership sustainability and firm risk - Sun, Jiong; Fang, Yiwei (Journal of Financial Stability, 2015)
This paper investigates the effect of management-level professional ties between suppliers and customers on the sustainability of business partnerships. We find that the presence of cross-firm professional ties between directors and senior executives along the supply chain significantly reduces the probability of relationship termination around customers’ industry negative shocks and during financial crises. The results are robust using professional-tie strength as an alternative measure. Exploring contingency effects, we find that, for suppliers who lack R&D, face high competition, are smaller in size, or are less important to customers in terms of sales, such professional ties are more helpful in sustaining such relationships. Furthermore, we find that professional ties also significantly reduce firm risk during periods of market turbulence. Taken together, our results suggest that professional ties along the supply chain can facilitate information flow and build mutual trust, which can lead to healthy long-term relationships and can help firms survive economic and industry downturns.